The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41467-018-05729-w
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-state plasticity is a targetable resistance mechanism in basal-like breast cancer

Abstract: Intratumoral heterogeneity in cancers arises from genomic instability and epigenomic plasticity and is associated with resistance to cytotoxic and targeted therapies. We show here that cell-state heterogeneity, defined by differentiation-state marker expression, is high in triple-negative and basal-like breast cancer subtypes, and that drug tolerant persister (DTP) cell populations with altered marker expression emerge during treatment with a wide range of pathway-targeted therapeutic compounds. We show that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
164
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(179 citation statements)
references
References 73 publications
(119 reference statements)
13
164
0
Order By: Relevance
“…While the model does not capture the rich behavior that may arise from the variable strengths of regulatory interactions in cells in a population or from cell-cell communication, it is a useful first step in understanding the generation and maintenance of phenotypic heterogeneity in cancer cells. Targeting the ability of cancer cells to change phenotypes and generate heterogeneous populations has recently been proposed as a therapeutic strategy for combating drug resistance (Risom et al, 2018). Our model can be a platform to identify putative therapeutic targets for inhibiting the generation, maintenance, and propagation of phenotypic heterogeneity in cancer cells that exhibit EMP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the model does not capture the rich behavior that may arise from the variable strengths of regulatory interactions in cells in a population or from cell-cell communication, it is a useful first step in understanding the generation and maintenance of phenotypic heterogeneity in cancer cells. Targeting the ability of cancer cells to change phenotypes and generate heterogeneous populations has recently been proposed as a therapeutic strategy for combating drug resistance (Risom et al, 2018). Our model can be a platform to identify putative therapeutic targets for inhibiting the generation, maintenance, and propagation of phenotypic heterogeneity in cancer cells that exhibit EMP.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous switching between luminal, basal, and stem-like states has been reported in breast cancer cell lines (Gupta et al, 2011) while androgen-deprivation therapy has been shown to promote transition to a neuroendocrine phenotype in prostate cancer (Hirano et al, 2004;Wright et al, 2003). Cancer cells with different phenotypes can exhibit different sensitivities to various drugs and therapeutic regimens (Risom et al, 2018;Wooten et al, 2018). Therefore, non-genetic mechanisms of phenotypic heterogeneity and plasticity in cancer cells are a fundamental challenge to anti-cancer therapies and an understanding of such mechanisms is essential to the development of effective anti-cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in cellular robustness, cell cycle progression, DNA damage response and induction of replication stress have been proposed as underlying mechanisms of response to BET inhibition (15,(17)(18). BET molecules also regulate cellular plasticity as exemplified by the emergence of drug-tolerant persistent cells with BRD4 dependence and altered differentiation states after MEK and PI3K/mTOR inhibition in TNBC (19). The adaptive responses and therapeutic stress such as DNA-damage associated with inhibition of BET activity provide an unexplored opportunity to discover drug-induced vulnerabilities, which might be exploited with effective combination therapies (20).…”
Section: Introductionmentioning
confidence: 99%